Linking talent management, knowledge management and work-life balance to employee performance: The role of job satisfaction - Andreas Wahyu Gunawan Putra; Riska Putri Cahyani (Jurnal Manajemen dan Pemasaran Jasa, 2024)
This research analyzes the influence of talent management, knowledge management, and work-life balance on employee performance, which is mediated by job satisfaction among employees of building equipment maintenance service companies. The data processing techniques employed included the testing of validity, reliability, and structural equation modeling (SEM) and the sample consisted of 190 employees. According to the findings, all hypotheses have been validated, indicating that employee performance can be enhanced through a comprehensive comprehension of talent management, knowledge management, and work-life balance. The novelty of this research lies in the integration of these three concepts in the specific context of the maintenance services industry, which has rarely been explored before, as well as the use of job satisfaction as a mediating variable that provides new insight into the relationship between human resource management and employee performance. Managerial implications show that good implementation of talent management and knowledge management, which supports work-life balance, will improve employee performance and job satisfaction, as well as help companies retain high-potential employees. The theoretical implication is that these concepts' integration as predictors of employee performance can be the basis for further theoretical framework development in human resources studies and open up further research opportunities in various industries and cultural contexts.